1998
DOI: 10.1093/nar/26.20.4662
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of a function of xeroderma pigmentosum group A (XPA) protein in strand-specific DNA repair

Abstract: To analyze the function of the xeroderma pigmentosum group A (XPA) protein in strand-specific DNA repair, we examined repair of UV-induced cyclobutane pyrimidine dimer (CPD) in transcribed and non-transcribed strands of the dihydrofolate reductase gene of xeroderma pigmentosum group A (XP-A) cell line (XP12ROSV) which was transfected with various types of mutant XPA cDNA. The transfectant overexpressing mutant XPA with a defect in the interaction with either ERCC1, replication protein A (RPA), or general trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 45 publications
3
24
0
Order By: Relevance
“…The repair of CPD was examined in the 17.9-kb KpnI fragment within the dihydrofolate reductase (DHFR) gene in XP4PASV cells transfected with control or BRCA1 siRNA and irradiated with 8 J ⁄ m 2 using a method previously described. (30) Briefly, DNA was extracted, digested with KpnI and treated with T4 endonuclease V, which generates single-strand breaks at CPD sites. The samples were separated by electrophoresis in 0.65% alkaline agarose gels, transferred onto Hybond N + membranes (Amersham Biosciences, Little Chalfont, Bucks, UK), and hybridized with strand-specific digoxigenin (DIG)-labeled DNA probes.…”
Section: Methodsmentioning
confidence: 99%
“…The repair of CPD was examined in the 17.9-kb KpnI fragment within the dihydrofolate reductase (DHFR) gene in XP4PASV cells transfected with control or BRCA1 siRNA and irradiated with 8 J ⁄ m 2 using a method previously described. (30) Briefly, DNA was extracted, digested with KpnI and treated with T4 endonuclease V, which generates single-strand breaks at CPD sites. The samples were separated by electrophoresis in 0.65% alkaline agarose gels, transferred onto Hybond N + membranes (Amersham Biosciences, Little Chalfont, Bucks, UK), and hybridized with strand-specific digoxigenin (DIG)-labeled DNA probes.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the role of the XPA interaction with RPA32 in NER, we prepared and examined the repair activities of mutant XPA proteins with N-terminal deletions. We have reported that the XP-A transfectant expressing a mutant XPA protein with a deletion of the N-terminal 36 amino acid residues (N⌬36) was more sensitive to UV irradiation than the transfectant expressing wild-type XPA and that the repair of the CPD is decreased in N⌬36-expressing cells (31).…”
Section: Analysis Of Mutant Xpa Proteins With N-terminal Deletions-mentioning
confidence: 99%
“…Several lines of evidence lead to the currently accepted hypothesis that the lesions are initially recognized by XPC with the help of UV-DDB (UV DNA damage binding protein) for cyclobutane pyrimidine dimer (CPD) lesions (17)(18)(19)(20) followed by damage verification by XPD/TFIIH (21)(22)(23)(24), XPA, and XPG (3) to finally assemble to the preincision complex (3,(25)(26)(27). This step seems to involve recruitment of the XPA protein, which is one of the proteins essential for both GG-NER and TC-NER (28). As such, mutations of the XPA proteins provide one of the strongest NER phenotypes (29).…”
mentioning
confidence: 99%
“…Initial structural insights into the protein architecture were derived from an NMR structure of the DNA binding domain of XPA (39,40). However, the precise structural basis of the interactions of XPA with its DNA substrates is not known (3,28).…”
mentioning
confidence: 99%